2014
DOI: 10.9734/bjesbs/2014/8417
|View full text |Cite
|
Sign up to set email alerts
|

Improving Literacy in the Transition Period: A Review of the Existing Evidence on What Works

Abstract: Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Therefore, dyslexia-specific interventions, which target these same socio-emotional skills but are explicitly framed around the experience of reading difficulties and consider the literacy skills of participants in the design of program materials, should also be developed and trialled. This may be particularly important in the context of stressful periods, such as the transition from primary to secondary school (Bailey & Baines, 2012;Eissa, 2010;Maguire & Yu, 2015;See & Gorard, 2014). Little research has examined the impact of interventions aiming to improve psychosocial health in children with dyslexia specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dyslexia-specific interventions, which target these same socio-emotional skills but are explicitly framed around the experience of reading difficulties and consider the literacy skills of participants in the design of program materials, should also be developed and trialled. This may be particularly important in the context of stressful periods, such as the transition from primary to secondary school (Bailey & Baines, 2012;Eissa, 2010;Maguire & Yu, 2015;See & Gorard, 2014). Little research has examined the impact of interventions aiming to improve psychosocial health in children with dyslexia specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Some reading interventions appear to be effective, at least for some struggling readers, but some do not (Hatcher et al ., ; Cantrell et al ., ). A prior review of existing evidence in this area for the EEF showed that one‐to‐one structured support was an area of promise (See and Gorard, ).…”
Section: Catch‐up Literacy Programmesmentioning
confidence: 97%
“…This paper looks at a body of evidence on a range of literacy interventions which have been evaluated, some of which show promise of positive results. Some reading interventions appear to be effective, at least for some struggling readers, but some do not or have not been tested properly (See and Gorard 2014). Specifically, this paper reports summary evidence on seven of the most promising or widely used interventions that could be used either when pupils are getting ready to leave primary school (in Year 6), or during the holiday between primary and secondary school, or when they first arrive in secondary school (Year 7).…”
Section: Introductionmentioning
confidence: 99%